2020
DOI: 10.15698/cst2020.03.214
|View full text |Cite
|
Sign up to set email alerts
|

RPA and Pif1 cooperate to remove G-rich structures at both leading and lagging strand

Abstract: In Saccharomyces cerevisiae, the absence of Pif1 helicase induces the instability of G4-containing CEB1 minisatellite during leading strand but not lagging strand replication. We report that RPA and Pif1 cooperate to maintain CEB1 stability when the G4 forming strand is either on the leading or lagging strand templates. At the leading strand, RPA acts in the same pathway as Pif1 to maintain CEB1 stability. Consistent with this result, RPA coprecipitates with Pif1. This association between Pif1 and RPA is affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Several accessory helicases have been implicated in replication of repetitive or structure-prone DNA (Anand et al, 2012; Sauer and Paeschke, 2017). In budding yeast, Pif1 has been shown to play an important role in allowing efficient replication past G4 sequences in vivo (Dahan et al, 2018; Lopes et al, 2011; Paeschke et al, 2011) and in vitro (Byrd et al, 2018; Maestroni et al, 2020; Paeschke et al, 2013; Ribeyre et al, 2009; Sparks et al, 2019b). We therefore assayed the ability of purified Pif1 to rescue DNA-induced stalled forks.…”
Section: Resultsmentioning
confidence: 99%
“…Several accessory helicases have been implicated in replication of repetitive or structure-prone DNA (Anand et al, 2012; Sauer and Paeschke, 2017). In budding yeast, Pif1 has been shown to play an important role in allowing efficient replication past G4 sequences in vivo (Dahan et al, 2018; Lopes et al, 2011; Paeschke et al, 2011) and in vitro (Byrd et al, 2018; Maestroni et al, 2020; Paeschke et al, 2013; Ribeyre et al, 2009; Sparks et al, 2019b). We therefore assayed the ability of purified Pif1 to rescue DNA-induced stalled forks.…”
Section: Resultsmentioning
confidence: 99%
“…These results also offer insights into previous studies wherein RPA was shown to stimulate the unwinding activity of FANCJ 20 , 47 . Given the variety of specialized G4 helicases and the known associations amongst some of them 19 , as well as with RPA 62 , 63 , it is likely that there is at least a partial redundancy in the roles of these helicases in assisting the RPA-mediated resolution of RF-coupled G4 formation like that observed for FANCJ. Indeed, a recent study in the Saccharomyces cerevisiae model system demonstrated that replication through G-rich minisatellites is enabled via a cooperation between RPA and the G4 helicase Pif1 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the variety of specialized G4 helicases and the known associations amongst some of them 19 , as well as with RPA 62 , 63 , it is likely that there is at least a partial redundancy in the roles of these helicases in assisting the RPA-mediated resolution of RF-coupled G4 formation like that observed for FANCJ. Indeed, a recent study in the Saccharomyces cerevisiae model system demonstrated that replication through G-rich minisatellites is enabled via a cooperation between RPA and the G4 helicase Pif1 63 . Further studies into the mechanisms governing RF-coupled G4 resolution in human cells are needed to clarify the specific contribution of different factors to these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the interaction of BLM and WRN with RPA was detected to suppress G4s in human cancer cell lines, facilitated by the HERC2 protein ( Wu et al., 2018 ). RPA and Pif1 were also reported to remove G4s coordinately at both leading and lagging strands in DNA replication in yeast cells ( Maestroni et al., 2020 ). These evidences then raise the important questions that helicases may require RPA to fulfill their function of resolving G4s.…”
Section: Introductionmentioning
confidence: 99%